A three-dimensional thermo-viscoelastic analysis of process-induced residual stress in composite laminates. (1st October 2015) - Ding, Anxin; Li, Shuxin; Wang, Jihui; Zu, Lei
Abstract: A three-dimensional thermo-viscoelastic model to simulate the residual stress in composite laminates during curing was proposed using the differential constitutive law. Based on a generalized Maxwell model with n Maxwell elements, a three-dimensional differential thermo-viscoelastic constitutive law was developed and corresponding differential finite element codes were incorporated into commercial software ABAQUS with an UMAT subroutine. In the present thermo-viscoelastic model the changes in thermal expansion, chemical shrinkage and stress relaxation were taken into account. The differential thermo-viscoelastic model and its finite element analysis were numerically validated in comparison to those presented by White and Kim (1998). Furthermore, the influence of aluminum skins on residual stress development for autoclaved composite laminates was evaluated with the present differential thermo-viscoelastic model. The results indicate that the aluminum skins have negligible effects on the cure of composite laminates and significant effects on the residual stress development during curing.